Calcium scoring during 18F-FDG PET/CT in cancer indications: Improving cardiovascular risk stratification and prevention - Réjane Mazet; Nouritza Torossian; Mathilde Wanneveich; Gilles Metrard; Angela Malmare; Denis Angoulvant; Matthieu Bailly (PLoS ONE, 2025)
Purpose Coronary artery calcium (CAC) can be assessed on 18F-FDG PET/CT in oncology patients. We evaluated the proportion of oncology patients referred for PET/CT imaging in whom systematic CAC scoring could reclassify cardiovascular (CV) risk and modify primary cardiovascular disease (CVD) prevention strategies. Materials and methods This prospective study included 190 cancer patients undergoing 18F-FDG PET/CT in oncological indications at our institution between June and July 2024. Data on CV risk factors, personal/family CVD history, and current treatments were collected. CAC scores were assessed visually and automatically on CT scans. Patients’ CV risk was reclassified according to CAC scores and compared with their current lipid-lowering therapy (LLT) and cardiology follow-up. Results A total of 190 subjects were analyzed (mean age 65 ± 13 years, 64% female, mean Framingham Risk Score 17.2 ± 9.2%). Patients were categorized as follows according to CAC: 24.7% (N = 47) no CAC, 36.8% (N = 70) mild, 21.6% (N = 41) moderate, and 16.8% (N = 32) severe CAC. Among them, 56.3% (N = 107) had a previous consultation with a cardiologist, 30.0% (N = 57) were on LLT, and 6.8% (N = 13) had a history of CVD. Based on CAC scoring, 43% (N = 81) could be reclassified in a different CVD risk category and 49% (N = 93) required changes in primary CVD prevention through LLT adjustments or initiating follow-up for high risk of CVD. Conclusion Systematic CAC assessment on PET/CT imaging could enhance CV risk stratification and prevention in oncology patients.